Adverse Event Profiles of PARP Inhibitors: Analysis of Spontaneous Reports Submitted to FAERS - Tian, Xiaojiang; Chen, Lin; Gai, Di; He, Sijie; Jiang, Xuan; Zhang, Ni (Frontiers in Pharmacology, 2022)
Background: Several poly ADP ribose polymerase inhibitors (PARPis) are currently approved for the treatment of a variety of cancers. The safety profile of PARPis has not yet been systemically analyzed in the real world. We conducted this pharmacovigilance analysis using the US FDA’s Adverse Event Reporting System (FAERS) database to explore the difference in adverse events (AEs) among PARPis. Methods: FAERS data (December 2014 to October 2021) were searched for reports of all FDA-approved PARPis across all indications. We used the standardized MedDRA query (SMQ) generalized search AEs on the preferred term (PT) level based on case reports. After filtering duplicate reports, disproportionality analysis was used to detect safety signals by calculating reporting odds ratios (ROR). Reports were considered statistically significant if the 95% confidence interval did not contain the null value. Results: Within the standardized MedDRA queries, significant safety signals were found, including those for olaparib [blood premalignant disorders (ROR=17.06)], rucaparib [taste and smell disorders (ROR=9.17)], niraparib [hematopoietic throbocytopenia (ROR=28.2)],and talazoparib [hematopoietic erythropenia (ROR=9.38)]. For AEs on the PT level, we found several significant signals, including platelet count decreased with niraparib (ROR=52.78); red blood cell count decreased with niraparib (ROR=70.47) and rucaparib (ROR=15.09); myelodysplastic syndrome with Olaparib (ROR=35.47); acute myeloid leukaemia with Olaparib (ROR=25.14); blood pressure fluctuation with niraparib (ROR=20.54); lymphangioleiomyomatosis with niraparib (ROR=471.20); photosensitivity reaction with niraparib (ROR=21.77) and rucaparib (ROR=18.92); renal impairment with rucaparib (ROR=33.32); and interstitial lung disease with Olaparib (ROR=11.31). All the detected safety signals were confirmed using signals of disproportionality reporting methods. Conclusion: PARPis differed in their safety profile reports. The analysis of the FAERS database revealed significant safety signals that matched previously published case reports, including serious gastrointestinal, blood and lymphatic system, cardiovascular and respiratory complications, which require individualized drug administration according to patients' conditions.